Transforming E-Commerce UX: A User-Centered Design Approach to Enhance Usability and Web Performance - Puti Agdira, MY Aura; Sari Setyaning Tyas; Yuyun Khairunnisa (Jurnal Kecerdasan Buatan dan Teknologi Informasi, 2026)
E-commerce platforms require optimal user interface (UI) and user experience (UX) alongside robust technical performance to retain users, particularly in specialized markets like mother-and-baby products. Initially, the Boonaboo e-commerce website exhibited critical deficiencies, achieving a poor System Usability Scale (SUS) score of 47.75 and a failing mobile Google Lighthouse performance score of 41. To address these dual challenges, this study implemented a comprehensive UI/UX redesign using the User-Centered Design (UCD) methodology. A mixed-methods, pretest-posttest evaluation was conducted involving 20 respondents, utilizing a novel dual-metric approach that combined subjective usability measurement (SUS) with objective technical auditing (Core Web Vitals via Google Lighthouse). Following the UCD intervention—which encompassed information architecture restructuring, navigation simplification, and asset optimization—the platform demonstrated remarkable enhancements. Mobile performance surged by 104.8% (from 41 to 84), while desktop performance reached near-perfection at 99. Concurrently, the mean SUS score escalated to 87.75, shifting the usability grade from Not Acceptable (Grade F) to Excellent (Grade A). These findings empirically prove that user-centered interface improvements inherently correlate with enhanced machine-measured web performance. This study contributes a validated dualmetric framework for evaluating e-commerce redesigns, offering actionable insights for optimizing digital retail environments where cognitive ease, speed, and user trust are paramount.